Consecuencias de la infestacion del tornillo, Xylotrechus arvicola (Olivier) (Coleoptera, Cerambycidae) - Ocete, R.=700 1 Salinas, J.A.; Soria, F.J.; Lara, M.; Garcia, D.; Maistrello, L.; Ocete, M.E.; Lopez, M.A.
(Es, En)
Ilus., 17 ref.
Keywords: COLEOPTERA; CERAMBYCIDAE; PLAGAS DE PLANTAS; DAÑOS; VID; PLANTAS LEÑOSAS; ESPAÑA; XYLOTRECHUS ARVICOLA; VIÑEDO; TORNILLO; BOLETIN DE SANIDAD VEGETAL: PLAGAS